Scope of Disciplinary Action Against Disciples: A Research Review in the Light of Sunnah and Islamic Jurisprudence - Khan, Janas; Muhammad Kamran (Journal of Islamic and Religious Studies, 2016)
Education is the development of the different aspects of human being like psychological, social and physical development etc. It is not only the provision of information but it is for the sake of guidance of students to make them beneficial human beings. A teacher inculcates good habits in students and tries to reduce or terminate bad habits in them. Therefore, the responsibility of teacher is to guide the students about good and bad along with improving their academics. But while doing so, the teacher should avoid the ways which can be harmful for the students. Therefore he (the teacher) should know how to guide the students and stop them from wrong doings. At what time what technique, he should adopt that can give benefits to students? He should be aware of the student’s psychology, their age and their abilities. Sometimes punishment is very much necessary for students to make them realize not to commit anything like this again. At this critical moment what can help the student and teacher? The Holy Prophet Muhammad (SAW), being a perfect teacher guided the Umma in this aspect. He used many skills as a teacher and taught his followers, how to guide their children and pupils. Many times the prophets would use to advise his followers on anywrong doing and that is why none of the followers repeated the same mistake. It is very important to follow the teachings of the Holy Prophet in aspect. This research paper discusses the way of handling the students in different situations.